2007
DOI: 10.1212/01.wnl.0000269791.96189.70
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital mortality of generalized convulsive status epilepticus

Abstract: Overall in-hospital mortality from generalized convulsive status epilepticus is low, but remarkably increases in those treated with mechanical ventilation. Other predictors of mortality include older age, female sex, hypoxic-ischemic brain injury, and higher comorbidity index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
113
6
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(141 citation statements)
references
References 19 publications
17
113
6
5
Order By: Relevance
“…In hospital seizure was also seen in other studies. 24 In present study 90% of children were brought to the casualty with seizure of 30 to 60 mins within the onset of seizure, Sachin Admuthe found that 74.07% of children was brought to casualty within 1 hour of onset of seizure. 23 It was observed that GTCS type of seizure is the commonest of all 4 types (66%) similar incidence was observed by Kwong KL 54% were generalized tonic clonic seizure, Gulati observed that 63.3% were generalized tonic clonic seizure.…”
Section: Discussionmentioning
confidence: 45%
“…In hospital seizure was also seen in other studies. 24 In present study 90% of children were brought to the casualty with seizure of 30 to 60 mins within the onset of seizure, Sachin Admuthe found that 74.07% of children was brought to casualty within 1 hour of onset of seizure. 23 It was observed that GTCS type of seizure is the commonest of all 4 types (66%) similar incidence was observed by Kwong KL 54% were generalized tonic clonic seizure, Gulati observed that 63.3% were generalized tonic clonic seizure.…”
Section: Discussionmentioning
confidence: 45%
“…En países en desarrollo, la mayoría de los estudios sobre EEC son retrospectivos y en el Perú hasta el momento no se han realizado estudios prospectivos de este problema de salud. En este estudio, al igual que en series prospectivas (8)(9)(10)(11)(12) y retrospectivas (13)(14)(15) de pacientes adultos admitidos en un hospital, la mayor proporción de pacientes con EEC fueron varones adultos jóvenes. A diferencia de estudios poblacionales (4)(5)(6) donde menos de la mitad de los pacientes con EE tienen antecedentes de epilepsia y la etiología sintomática aguda es más frecuente, en este y otros estudios prospectivos hospitalarios (11,12) más del 60% de los pacientes tenían antecedentes de epilepsia y eran usuarios de drogas antiepilépticas y en más de la mitad de los casos la causa más frecuente del EEC fue el incumplimiento de la medicación antiepiléptica.…”
Section: Discussionunclassified
“…Por otra parte, mientras en países desarrollados, el accidente cerebrovascular es la causa sintomático aguda predominante (6,10,11) , en países en desarrollo las infecciones del SNC representan el espectro etiológico agudo más frecuente (8,12) , En nuestra serie un 21% de los casos tuvieron una etiología sintomática aguda, siendo las infecciones del SNC las más frecuentes. Cabe destacar que cuatro pacientes con EEC por etiología sintomática aguda tenían antecedentes de epilepsia, en todos ellos la causa del EEC fue una infección del SNC (uno por encefalitis viral y tres por neurocisticercosis).…”
Section: Discussionunclassified
See 2 more Smart Citations